DETECTION OF ALKALOID, FLAVONOID, AND TERPENOID COMPOUNDS IN BREAD (Artocarpus communis Forst.) LEAVES AND PULPS - Kristanti, Handriani (2014)
Leaves of bread tree (Sukun/ Artocarpus communis Forst.) can be used to cure skin diseases, heart, kidneys, and inflamation. The advantageous of bread might be related with its secondary metabolite compounds. The purpose of this research was to detect and compare the content of alkaloid, flavonoid, and terpenoid compounds in bread leaves and pulps using Thin layer Chromatography (TLC) methods. The coloring reagents were dragendorf for alkaloid, sitroborat for flavanoid and sulfate vanillin for terpenoid. Reference compounds used for alkaloid is quinine, rutine for the flavonoid, and terpeniol for terpenoid. The result indicated that alkaloid were detected in chloroform extracts of leaves with Rf score 0.76 and methanol extracts with Rf 0.8, while the alkaloid in pulps weren’t detected. This showed that the leaves were contain of polar and nonpolar alkaloid. Flavonoid were detected in leaves with Rf value 0.89 and in pulps with Rf value 0.9. This result indicated that flavonoid in the leaves and pulps possibly the same compound. Terpenoid were detected in the methanol and chloroform extract of leaves (4 spots) and pulps (2 spots). Moreover, there were spots which have the same Rf value in chloroform and methanol extracts of the leaves (Rf :0,625 and 0,99). In addition, the pulps extracts (chloroform and methanol) have the same Rf values with reference, that was 0,31. It was proved that the pulps contain terpeniol. It can be concluded that alkaloid was only detected in leaves, while flavonoid and terpenoid present in leaves and pulps of bread tree.